The field beyond the outfield - Teague, Mark. (New York : Scholastic Inc., 1991)
When Ludlow begins to play baseball to help combat his fears, he is placed so far out in the outfield that he becomes involved with an adjacent game in which a most astonishing thing happens.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
3.8
K-3
Keywords: Fear -- Fiction; Baseball -- Fiction; Fear -- Fiction; Baseball -- Fiction; Fear -- Fiction; Baseball -- Fiction